Страхування відповідальності при наданні професійних послуг - Nykyforak, Volodymyr; Никифорак, Володимир Михайлович (Чернівецький національний університет. Видавництво "Рута"., 2006)
In clause the features of accomplishment of liability insurance at rendering professional services are analyzed. For more detailed disclosure of a researched question the author has taken advantage of examples of insurance of the professional responsibility of the notaries.
Keywords: страхування; договір страхування цивільно-правової відповідальності; послуги; страхування професійної відповідальності